Challenges and Strategies of Citizenship Education Learning in Elementary Schools - Widyadhari, Bulan (International Journal of Students Education, 2025)
Civic Education (PKN) in Elementary Schools plays an important role in shaping the character and awareness of nation and state in the younger generation. However, in its implementation, there are various challenges faced, including students' lack of understanding of basic citizenship concepts, low motivation to learn, and limited media and resources in the learning process. This journal aims to identify the challenges faced in the implementation of Citizenship Education (PKN) learning in Elementary Schools and develop effective learning strategies to overcome the challenges. The results of the study identified several major challenges, such as low student interest, limited learning methods and media, obstacles in mastering technology, and less relevant learning contexts. To address these challenges, several strategies are proposed, including project-based learning approaches, technology integration, collaborative methods, and contextualization of materials. With the implementation of these strategies, it is expected that civics learning will be more effective and increase student motivation and engagement. These findings have important implications for the development of educational policies and civics teaching practices in Indonesia in facing challenges in elementary schools. This research method is a type of qualitative research that uses a literature study method or literature review, and uses a data collection method that uses a literature review method. The conclusion of this study is that civics education (PKn) learning in elementary schools faces various challenges, to overcome these challenges, innovative and participatory learning strategies are needed